2020
DOI: 10.2147/jaa.s275944
|View full text |Cite
|
Sign up to set email alerts
|

<p>Real-World Reductions in Oral Corticosteroid Use in the USA Following Mepolizumab Therapy for Severe Asthma</p>

Abstract: Background Patients with severe asthma often require oral corticosteroid (OCS) treatment. Clinical trials have demonstrated that mepolizumab can reduce OCS dependence, but real-world data are limited. Objective To evaluate the impact of mepolizumab on OCS use, asthma exacerbations, and asthma exacerbation-related costs in a real-world setting. Methods This retrospective cohort study (GSK ID: 209642; HO-19-19597) analyzed data from the MarketS… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
19
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 18 publications
(23 citation statements)
references
References 21 publications
(40 reference statements)
4
19
0
Order By: Relevance
“…Indeed, the large real-world evidence on omalizumab may be related to the fact that this mAb has been present on the market for a longer time than the other mAbs included in this systematic review. Interestingly, data on mepolizumab reported from very large and long-term realworld studies [42,50,56] were generally consistent with those obtained for omalizumab with respect to both the percentage of patients that discontinued OCS and the reduction in the daily dose of OCS in those patients that still required maintenance OCS to control the disease. The only very large study [85] on reslizumab also confirmed that mAb therapy is able to halve the percentage of patients requiring maintenance OCS, although reslizumab reduced the daily dose of OCS slightly less than omalizumab and mepolizumab among the patients that continued to need OCS.…”
Section: Discussionsupporting
confidence: 69%
See 3 more Smart Citations
“…Indeed, the large real-world evidence on omalizumab may be related to the fact that this mAb has been present on the market for a longer time than the other mAbs included in this systematic review. Interestingly, data on mepolizumab reported from very large and long-term realworld studies [42,50,56] were generally consistent with those obtained for omalizumab with respect to both the percentage of patients that discontinued OCS and the reduction in the daily dose of OCS in those patients that still required maintenance OCS to control the disease. The only very large study [85] on reslizumab also confirmed that mAb therapy is able to halve the percentage of patients requiring maintenance OCS, although reslizumab reduced the daily dose of OCS slightly less than omalizumab and mepolizumab among the patients that continued to need OCS.…”
Section: Discussionsupporting
confidence: 69%
“…The only very large study [85] on reslizumab also confirmed that mAb therapy is able to halve the percentage of patients requiring maintenance OCS, although reslizumab reduced the daily dose of OCS slightly less than omalizumab and mepolizumab among the patients that continued to need OCS. However, we have to highlight that the daily dose of OCS at baseline in the very large studies on omalizumab [74,78,82] and mepolizumab studies [42,50,56] were generally lower than that of the very large study on reslizumab [85]. Only one large real-world study [34] has been carried out on benralizumab, which permitted OCS consumption to be abolished in all the observed patients.…”
Section: Discussionmentioning
confidence: 91%
See 2 more Smart Citations
“…The low prevalence of CU in SA, which is 0.9% and 5.6% in SEA patients treated with mepolizumab and in allergic SA patients treated with omalizumab, respectively, could be involved in this paradox. Moreover, these studies did not provide information neither on the severity nor on the response of CU to asthma treatment [4][5].…”
mentioning
confidence: 98%